A Deadly Hotel Fire Incident: Case Series Of Carbon Monoxide Poisoning And Literature Overview (Journal of Forensic Medicine & Toxicology, 2026)
Carbon monoxide (CO) poisoning is a significant global public health concern, often resulting in severe health conse quences or fatalities. This report examines eight fatal cases of CO poisoning caused by a hotel fire, highlighting the com plexity of CO exposure in fire-related incidents. The fire, originated in a basement used for commercial purposes and fueled by flammable materials. It rapidly escalated, causing widespread panic and trapping guests due to a sudden power outage. Post-mortem examinations revealed that all victims exhibited characteristic signs of CO poisoning, including cherry-red discoloration of tissues, soot in the respiratory tract, and elevated carboxyhemoglobin levels. Histopathological analysis of lung tissues showed congestion and black pigmentation, consistent with CO exposure. Chemical analysis con firmed significant CO levels in the victims’ blood. This incident underscores the critical need for stringent fire safety measures, including proper use of building spaces, functional emergency lighting, smoke detectors, and regular safety inspections. The findings demonstrate that CO poisoning, combined with smoke inhalation, is often more lethal than burns alone. The study reveals important features in cases of CO poisoning and also emphasizes the need for stricter adherence to fire safety regulations and improved safety protocols to prevent similar tragedies in the future.
Keywords: Carbon monoxide (CO); CO poisoning; Carboxyhemoglobin (COHb); Fire incident